ESTIMATED HBA1C AND FASTING GLUCOSE INDICES FOR DIABETES AND PREDIABETES SCREENING QUESTIONNAIRE EVALUATION - Agasafa oglu, Mirzazade Valeh; Zalimkhan kizi, Aliyeva Aygun; Sabir kizi, Sultanova Sadagat; Nusrat kizi, Guseynova Nargiz (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2025)
Objective. The aim of this study is to develop new indicators, estimated HbA1c and fasting glucose index, for early detection of diabetes mellitus and prediabetes using questions from various questionnaires based on anamnestic and anthropometric data. Methods and participants. A total of 182 individuals aged 20–79 years (46 men and 136 women) participated in the study. All participants underwent diabetes screening questionnaires, anthropometric measurements, and blood pressure assessments. HbA1c levels were measured using the SDA1c Care analyzer (SD Biosensor, Korea). Fasting and post-load venous plasma glucose levels were determined using the Precision PCx MediSense analyzer (Abbott, USA). A 75 g oral glucose tolerance test (OGTT) was performed for all participants. The following variables were used to calculate the ScrHbA1c and ScrFG indices through multiple linear regression analysis: anamnesis score, age, waist circumference, systolic, and diastolic blood pressure. Chi-square tests were used to compare categorical variables. Diagnostic performance of the ScrHbA1c and ScrFG indices was evaluated using standard measures: sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), overall diagnostic accuracy, and the Youden Index to determine optimal cut-off points. Results. A statistically significant correlation was observed between measured fasting glucose levels and the ScrFG index in both groups: training group: r = 0.52, p < 0.001, and control group: r = 0.41, p < 0.001. Similarly, a strong and statistically significant correlation was found between measured HbA1c and the ScrHbA1c index: training group (n = 91): r = 0.5462, p < 0.001, and control group (n = 91): r = 0.51, p < 0.001. Both ScrHbA1c and ScrFG index values were significantly higher in individuals with impaired glucose metabolism (diabetes + prediabetes) than in those with normal glucose metabolism, in both the training and control groups (p < 0.001 for both comparisons). No significant differences in ScrHbA1c or ScrFG values were observed between the training and control groups within subgroups of normal or impaired glucose metabolism (p > 0.05). Conclusion. The values of the newly proposed indicators, ScrHbA1c and ScrFG, showed significant correlation with measured HbA1c and fasting glucose levels. Using a cut-off point of 125 mg/dL for ScrFG enabled the identification of 100% of diabetes cases, 67.4% of prediabetes cases, and 83% of individuals with normal carbohydrate metabolism. Similarly, applying a cut-off point of 44 mmol/mol for ScrHbA1c allowed for the detection of 100% of diabetes cases, 69.6% of prediabetes cases, while also recommending further examination for 20% of individuals without carbohydrate metabolism disorders. These newly developed indicators ScrHbA1c and ScrFG are intended to facilitate the preliminary selection of individuals who should undergo screening for diabetes and prediabetes.